PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Perbankan yang Terdaftar di BEI 2009-2013) - Yanto Hans Pratama; Tarmizi Achmad (Diponegoro Journal of Accounting, 2015)
This study aims to empirically examine the effect of VAIC on the performance of firm and company size as a moderating variable in the relationship between VAIC and Competitive Advantage. Firm performance used in this study measured using Return On Asset (ROA), return On equity (ROE) and Asset Growth. While firm size is measured by using the total number of company assets and intellectual capital is measured using VAIC ™ method developed by Pulic (1998 ) .This study used a sample of banking companies listed on the Stock Exchange period 2009-2013 using purposive sampling method . The data used were obtained from the annual financial statements of banking companies listed on the Stock Exchange. There are 38 companies and 135 observations over the years 2009-2013.However, because there were the outlier data, finally the data taht used were 86 sample. The method of analysis used in this study is multiple regression analysis . This method was chosen because all of the data is matrix variable.In the statistical results of the study found that VAIC significantly affect the Competitive Advantage. Intellectual Capital and Competitive Advantage significantly affect to Return On Asset(ROA), Return On Equity (ROE) but not to the Asset Growth(AG).